Intraannular photoreactions in pseudo-geminally substituted [2.2]paracyclophanes - Hopf, Henning; Raev, Vitaly; Jones, Peter G. (Beilstein Journal of Organic Chemistry, 2011)
The photoisomerization of the pseudo-geminal tetraene 11 furnishes the cyclooctadiene derivatives 13 and 15 with a completely new type of molecular bridge for a [2.2]paracyclophane which promise many interesting novel applications; the same is true for the photoisomerization of 22 to 23 and 24. The structures of these new hydrocarbons were established by X-ray crystallography and spectroscopic analysis; among the noteworthy structural features of 13 and 15 are unusually long carbon–carbon single bonds (>1.64 Å).
Keywords: paracyclophanes; photoadditions; photoisomerizations; proximity effects; topochemical reaction control; vinylcyclopropanes; X-ray structural analysis